Asymmetrical loading of lead and lag legs during landings of blocking movements - McNitt-Gray, J. L.; Munkasy, B. A.; Mathiyakom, W.; Hillman Somera, N.
1. Prepare athlete for asymmetrical loading between legs through task-specific training. Choose closed chain exercises of the lower limb that replicate the desired movement pattern (segment orientation, foot position relative to the knee, rate and range of joint flexion/extension and coordination between adjacent joints). For Example: Single-leg step downs or lunges in multiple directions that replicate movements an individual leg typically experiences (forward, backward, laterally, diagonally). As with all exercise, a balance between loading and recovery must be established to avoid overuse injury. 2. Be aware of potential asymmetries in loading between legs when designing practice activities and drills. Note degree of asymmetrical loading may vary between subjects, tasks and potentially, fatigue levels. 3. When setting up a strengthening exercise program, either for asymmetrical, bilateral or unilateral loading exercises, watch out for signs of an overuse injury. Only a delayed onset of muscle soreness is acceptable. 4. Due to asymmetrical loading, fatigue of the lead leg may occur. Conditioning endurance training should be included in the training program. Again, any signs of an overuse injury need to be monitored.